Process optimization via response surface methodology in the treatment of metal working industry wastewater with electrocoagulation - Guvenc, Senem Yazici; Okut, Yusuf; Ozak, Mert; Haktanir, Birsu; Bilgili, Mehmet Sinan (IWA PUBLISHING, 2017)
In this study, process parameters in chemical oxygen demand (COD) and turbidity removal from metal working industry (MWI) wastewater were optimized by electrocoagulation (EC) using aluminum, iron and steel electrodes. The effects of process variables on COD and turbidity were investigated by developing a mathematical model using central composite design method, which is one of the response surface methodologies. Variance analysis was conducted to identify the interaction between process variables and model responses and the optimum conditions for the COD and turbidity removal. Second-order regression models were developed via the Statgraphics Centurion XVI. I software program to predict COD and turbidity removal efficiencies. Under the optimum conditions, removal efficiencies obtained from aluminum electrodes were found to be 76.72% for COD and 99.97% for turbidity, while the removal efficiencies obtained from iron electrodes were found to be 76.55% for COD and 99.9% for turbidity and the removal efficiencies obtained from steel electrodes were found to be 65.75% for COD and 99.25% for turbidity. Operational costs at optimum conditions were found to be 4.83, 1.91 and 2.9 (sic)/m(3) for aluminum, iron and steel electrodes, respectively. Iron electrode was found to be more suitable for MWI wastewater treatment in terms of operational cost and treatment efficiency.
Keywords: aluminum-iron-steel electrodes; cost analysis; electrocoagulation; response surface methodology; ELECTROCHEMICAL TREATMENT; REMOVAL; EMULSIONS; FLUIDS; Engineering; Environmental Sciences & Ecology; Water Resources